Information Transmission Efficiency Versus Position of A Geostationary Satellite - Bogdan ULJASZ (Communications of International Proceedings, 2021)
Despite the highly developed fiberoptic infrastructure, satellite communications ensure the transmission of information from anywhere on Earth. In the article, a proposal to increase the efficiency of information transmission in satellite links based on geostationary satellites is presented. Practical measurements of satellite links carried out from Polish territory through various satellites are presented in this article. Several days of measurement results of a single satellite link show large fluctuations in the quality of information transmission. Therefore, the use of satellite selection for the transmission of information is the basis of the solution presented in this article. The design procedure for choosing the optimal satellite link is summarized.
Keywords: Satellite Communications; Measures of The Quality of Information Transmission.